Food Photography Training as a Digital Promotion Strategy Based on the Global Code of Ethics for Tourism for Students of SMKN 1 Leuwimunding, Majalengka Regency - Siti Zakiah; Ilham Fajri; Dika Dwi Panji; Eva Mardiyana; Vany Octaviany (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The development of digital technology has transformed tourism promotion patterns, including the culinary industry, which increasingly relies on attractive visual content through social media platforms. This community service program aims to enhance students’ competencies in utilizing food photography as an ethical and sustainable digital promotion strategy based on the principles of the Global Code of Ethics for Tourism. The program was conducted for students of SMKN 1 Leuwimunding, located in Majalengka Regency. The methods implemented in this program included lectures on food photography, the utilization of digital media, practical food photography sessions, and the internalization of tourism promotion ethics based on the Global Code of Ethics for Tourism. The results of the program are expected to demonstrate an improvement in students’ understanding of food photography techniques, digital marketing strategies, and awareness of the importance of responsible promotion that respects local culture and supports sustainable tourism. Furthermore, this program is expected to foster a generation of young individuals who are not only technically competent but also possess ethical awareness in digital tourism promotion.